The direct foreign investment process in Turkish manufacturing - Asim Erdilek (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1980)
The direct foreign investment (DFI) process refers collectively to the initiation and formalization of the DFI idea, the application to and negotiations with the host-country government for DFI authorization, the implementation of the DFI project, and its actual private profitability relative to the initial and present expectations of the investors. Throughout the analysis of our quantitative findings, we will frequently refer to the results of our interviews with the executives of DFI firms and Turkish government officials. Our objective in doing so will be both to compare the questionnaire results with those of the interviews and to clarify the former in terms of the latter.
Keywords: 330